2004
DOI: 10.1103/physreve.69.021710
|View full text |Cite
|
Sign up to set email alerts
|

Swelling dynamics of liquid crystal elastomers swollen with low molecular weight liquid crystals

Abstract: We experimentally investigated the swelling behavior of thin films (approximately 150 microm) of liquid crystalline elastomers (LCEs) by low molecular weight liquid crystals (LMWLCs). The two LMWLCs used are the well-known nematic liquid crystals, 4-n-pentyl-4-cyanobiphenyl, and 4-methoxy-benzilidene-4-butyl-aniline. Both polydomain (POLY) and monodomain (MONO) LCE swelling are studied. In MONO LCEs (LSCEs), the director n empty set is uniformly oriented throughout the film. POLY films are made of many domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 13 publications
2
53
1
2
Order By: Relevance
“…No dimension changes parallel to the director n could be observed during the swelling in 8A2 [6]. We believe this is because the crosslinkers in that LCE system order essentially parallel to the tethered mesogenic side chains due to their chemical constitution (the mesogenic units are oriented parallel to the stretching direction, fix a length scale in kn n), resulting in networks with 'equasi-smectic' ordering, i.e., larger frozen-in orientational order (FOO) [6]. In contrast, V3LSCE swells in kn n because its cross-linker (trifunctional type) has isotropic-like property which reducing the degree of FOO [7], comparing to the bifunctional cross-linker which has anisotropic property.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…No dimension changes parallel to the director n could be observed during the swelling in 8A2 [6]. We believe this is because the crosslinkers in that LCE system order essentially parallel to the tethered mesogenic side chains due to their chemical constitution (the mesogenic units are oriented parallel to the stretching direction, fix a length scale in kn n), resulting in networks with 'equasi-smectic' ordering, i.e., larger frozen-in orientational order (FOO) [6]. In contrast, V3LSCE swells in kn n because its cross-linker (trifunctional type) has isotropic-like property which reducing the degree of FOO [7], comparing to the bifunctional cross-linker which has anisotropic property.…”
Section: Introductionmentioning
confidence: 80%
“…They were swollen with a low molecular weight liquid crystals, 4-n-pentyl-4-cyanobiphenyl (5CB), an anisotropic solvent. In particular, we found that the swelling properties and temperature behavior (thermomechanical property) of volume changes were also anisotropic [5][6][7]. The magnitude of the swelling anisotropy depended on the cross-linking concentration.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…If the solvent has nematicity, the nematic order of the surrounding solvent also influences the swelling. [9][10][11][12] These swelling behaviors are governed by the orientational orders of the constituent LCs, and they are described by a mean field theory. [13][14][15][16] The characteristic swelling dynamics was also revealed by the temperature-jump experiments.…”
Section: Introductionmentioning
confidence: 99%